2011
DOI: 10.1038/bjc.2011.159
|View full text |Cite
|
Sign up to set email alerts
|

An increase in cancer stem cell population after primary systemic therapy is a poor prognostic factor in breast cancer

Abstract: Background:The cancer stem cell (CSC) hypothesis has important clinical implications for cancer therapeutics because of the proposed role of CSCs in chemoresistance. The aim of this study was to investigate changes in the CSC populations before and after primary systemic therapy (PST) and their prognostic role in human breast cancer.Methods:Paired samples (before and after PST) of breast cancer tissue were obtained from clinical stage II or III patients (n=92) undergoing PST with the regimen of doxorubicin plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(152 citation statements)
references
References 44 publications
14
135
0
3
Order By: Relevance
“…The clinical relevance of these results is underscored by studies demonstrating associations between: (i) ALDH expression and ER − /basal subtype breast cancer (51); (ii) HIF-1α and ALDH + cells in breast cancers, both before and after chemotherapy (51); (iii) ALDH + breast cancer cells and resistance to sequential paclitaxel and epirubicin chemotherapy (52); and (iv) increased ALDH + cells after chemotherapy and decreased disease-free survival (51,53). Taken together with these clinical studies, our results provide compelling evidence in support of clinical trials combining HIF inhibitors and cytotoxic chemotherapy in women with TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of these results is underscored by studies demonstrating associations between: (i) ALDH expression and ER − /basal subtype breast cancer (51); (ii) HIF-1α and ALDH + cells in breast cancers, both before and after chemotherapy (51); (iii) ALDH + breast cancer cells and resistance to sequential paclitaxel and epirubicin chemotherapy (52); and (iv) increased ALDH + cells after chemotherapy and decreased disease-free survival (51,53). Taken together with these clinical studies, our results provide compelling evidence in support of clinical trials combining HIF inhibitors and cytotoxic chemotherapy in women with TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of tumor samples revealed that only 1% of the ALDH-positive cell population had the CD44 + /CD24 −/low /Lineage − phenotype reported for BCSCs (2). In fact, an increase in the population of ALDH1-positive cells but not CD44 + /CD24 −/low cells has been observed in breast cancer tumor biopsies after neoadjuvant treatment (56). Considering the limited usefulness of ALDH1 activity as a sole marker of BCSCs, other combinations have been studied, such is the CD44 + /ALDH1 +/high phenotype.…”
Section: Cd44 + /Aldh1 +/High Phenotypementioning
confidence: 98%
“…27 These biomarkers are associated with increased resistance to chemotherapy, [3][4][5] tumorigenesis, 1 and poor prognosis. 28,29 Therefore, we sought to determine if culture on nanofiber scaffolds could increase the CD44…”
Section: Enrichment Of Bcsc Populations In Cells Cultured On Pcl-cs Nmentioning
confidence: 99%